THE RECOVERY OF MORE ENNIUS FROM A MISINFORMED CICERONIAN SCHOLIAST*. (16th April 2014) - Ramsey, John T.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this paper is to propose a new and more satisfactory context for a fragment from one of Ennius' tragedies preserved in Cicero and discussed by a late scholiast on the Ciceronian passage. It will be shown that the scholiast, or more likely the source upon which he drew, had in front of him a bit more of the Ennian passage than the partial line preserved in Cicero and that the scholiast drew a false conclusion concerning the identity of one of the interlocutors from the way in which one speaker addressed the other. Previous scholars have sought to remove the inconsistency in the scholiast's sketch of the scene either by changing the locale of the dialogue or by correcting the scholiast's identification of the out-of-place speaker. It will be shown that a more productive line of investigation is to seek to discover the underlying cause of the scholiast's apparent error. The identification of the cause not only sheds light on the fate of Ennius' text in Late Antiquity but permits us to restore, by means of conjecture, an additional word to the corpus of Ennius' tragedies, a word that is a favourite of his in the Annales, but until now has not been attested in a Roman tragedy before the age of Seneca.